Formulation and Characterization of Edible Film with Concentration Various of Sodium Carboxymethyl Cellulose from Kepok Banana (Musa paradisiaca L.) Bark and Plasticizer - Ningsi, Surya; Abbas, Nurfahima; Arsul, Muhammad Ikhlas (Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction: Bark of kepok banana (Musa paradisiaca L.) contains high cellulose that can be synthesized into sodium carboxymethyl cellulose (Na-CMC). Na-CMC can be used as a raw material for the preparation of edible film. Aims: The purpose of this study was to determine the concentration of sodium carboxymethyl cellulose from kepok banana bark combine with plasticizer to produce edible films with good characteristics and quality. Methodology: Edible films were made with varying concentrations of 6%, 10%, and 14% Na-CMC; 4% glycerol and 9% sorbitol as plasticizer. Edible films were made using casting method and characterized including organoleptic test, thickness, pH, water absorption, elongation, and tensile strength. Result: Edible film made is in the form of thin layer, transparent white in color, and odorless; thickness 0,10±0,01-0,38±0,01 mm; pH 7,1±0,08-7,7±0,04; moisture content 35,47-91,97%; elongation 16,33±3,66-53,29±6,13%; and tensile strength 0,0528±0,00-3,9871±0,04 MPa.. Conclusion: Different concentrations of Na-CMC and plasticizer affect the characteristics produced. The best result based on Japanese Industrial Standard (JIS) is formula F5 with 10% Na-CMC concentration and 9% sorbitol as plasticizer